2021
DOI: 10.1101/2021.02.10.430513
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuromesodermal progenitor origin of trunk neural crestin vivo

Abstract: Neural crest (NC) is a vertebrate-specific population of multipotent embryonic cells predisposed to particular derivatives along the anteroposterior (A-P) axis. While only cranial NC progenitors give rise to ectomesenchymal cell types, trunk NC is biased for neuronal cell fates. By integrating multimodal single-cell analysis we uncovered heterogenous NC cells across the entire A-P axis expressing NC regulator foxd3. We pinpointed to its specific cranial and trunk auto-regulated enhancers. The trunk foxd3 enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…Together this work suggests that the CNS and derivatives of trunk/sacral NC (such as the peripheral nervous system) arise from a common PNP derived from the NMP population. This finding has recently been supported by studies in vivo (Lukoseviciute et al, 2021). Surprisingly, the addition of the BMP inhibitor LDN did not prevent NC specification in long-term PNPs, although only intermediate levels of BMP signaling are required to robustly induce NC commitment (Frith et al, 2018;Hackland et al, 2017).…”
Section: Discussionmentioning
confidence: 73%
“…Together this work suggests that the CNS and derivatives of trunk/sacral NC (such as the peripheral nervous system) arise from a common PNP derived from the NMP population. This finding has recently been supported by studies in vivo (Lukoseviciute et al, 2021). Surprisingly, the addition of the BMP inhibitor LDN did not prevent NC specification in long-term PNPs, although only intermediate levels of BMP signaling are required to robustly induce NC commitment (Frith et al, 2018;Hackland et al, 2017).…”
Section: Discussionmentioning
confidence: 73%
“…More recently, using a trunk-specific foxd3 enhancer to trace the lineage of NC cells in vivo, tailbud NMPs were also labeled. Subsequently, labeling was encountered in cells that express neural plate border and early NC genes and in neuronal trunk derivatives such as dorsal root ganglia [8]. Together, these results suggest that at least some trunk-level NC progenitors also derive from NMPs.…”
Section: Introductionmentioning
confidence: 86%
“…An intriguing question is what NC populations emanate from NMPs [8], are these primarily neural progenitors or also melanocytes? Additional labeling strategies should be implemented to address the lineage of the trunk NC back to these fascinating postgastrulation progenitors, followed by exploring mechanisms of lineage segregation.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Similarly, lineage tracing of cells expressing NMP markers such as Nkx1–2 , Tbx6/Sox2 , Bra/T and FoxB1 revealed that these contribute to neural, mesodermal and NC lineages [ 58 , 61 , 63–68 ]. More recent work, using single-cell transcriptomics and epigenomic profiling in zebrafish, has further demonstrated that posterior NC is derived from an NMP-derived pre-neural intermediate [ 69 ]. Taken together these data strongly suggest that, at least a fraction of trunk and sacral NC are directly derived from axial progenitors, which are competent to generate presomitic mesoderm.…”
Section: The Development Of Nc and Its Derivatives In Vivomentioning
confidence: 99%